Ground-based millimetre-wave measurements of middle-atmospheric carbon monoxide above Ny-Ålesund (78.9° N, 11.9° E) - Ryan, Niall J.; Palm, Mathias; Hoffmann, Christoph G.; Goliasch, Jens; Notholt, Justus (Atmospheric Measurement Techniques, 2019)
We present a new ground-based system for measurements of middle-atmospheric carbon monoxide (CO) at Ny-Ålesund, Svalbard, and the altitude profiles of CO volume mixing ratios (VMRs) measured during the 2017/2018 winter. The Carbon Monoxide Radiometer for Atmospheric Measurements (CORAM) records spectra from CO spectral emissions in the middle atmosphere with the aid of a low-noise amplifier designed for the 230 GHz spectral region. Altitude profiles of CO VMRs are retrieved from the measured spectra using an optimal estimation inversion technique. The profiles in the current dataset have an average altitude range of 47–87 km, with special consideration to be given to data at >∼70 km altitude. The estimated uncertainty in the CO profile peaks at ∼12 % of the a priori data used in the inversion. The CORAM profiles are compared to co-located CO measurements from the Microwave Limb Sounder (MLS) aboard the Aura satellite and show a difference of 7.4–16.1 %, with a maximum absolute difference of 2.5 ppmv at 86 km altitude. CO profiles are currently available at 1 h resolution between November 2017 and January 2018. The instrument measures during Arctic winter because summer time CO concentrations are so low as to be undetectable by CORAM.